KÜRESELLEŞME VE KENT YOKSULLUĞU OLGUSUNA SOSYOLOJİK BİR YAKLAŞIM - YILMAZ, MEVLÜT (Fırat Üniveristesi, 2010)
Yoksulluk, yirmi birinci yüzyılın ilk yıllarını yaşadığımız bu günlerde küreselleşme sürecinin etkisiyle içinden çıkılmaz bir duruma doğru evirilmektedir. Tüm alanlarda yaşanan değişim, dönüşüm doğal bir şekilde kendini toplumdaki problemlere de yansıtmaktadır. İnsanlığın var oluşuyla yaşıt kabul edebileceğimiz yoksulluk olgusu, gün geçtikçe yeni boyutlar kazanmakta ve özellikle küreselleşme çağında değişen dünyada kendi payına düşeni fazlasıyla almaktadır.Küreselleşme ile birlikte kent yoksulluğu olgusu daha da önemli hale gelmektedir. Kentleşme oranlarının artması yanında ekonomik alanda yaşanan post ? fordist dönüşüm beraberinde işsizlik, ücretlerin düşürülmesi, taşeronlaştırma v.b sorunlar beraberinde kent yoksulluğuna yol açmaktadır. Bu çalışmada, küreselleşen dünyada gün geçtikçe derinleşen yoksulluk konusu, kent yoksulluğu bağlamında irdelenmektedir. Küreselleşme çağında yeni boyutlar kazanan yoksulluk olgusu, kent yoksulluğu çerçevesinde ele alınırken gelişmiş ülkelerin gökdelen altlarında, sokaklarda ve köprü altlarında karton kutularda yaşayan, çöplerden beslenen, potansiyel suçlu olarak görülen bireyler artık küresel kentler başta olmak üzere tüm büyük şehirlerin gerçeği haline gelmektedir.Buradan hareketle kentsel yoksulluk sorunu, gerek ulusal gerekse de uluslararası alanda toplumsal bir problem olarak gün geçtikçe kronikleşen bir hâl almaktadır. Küresel dünyanın kentleri varsıl-yoksul arasındaki uçurumun en net gözlemlendiği yerler olarak dikkat çekici öneme sahiptir. Bunun için de özellikle kentlerin, yoksulluğun oluşumu ve gelişimine etkisi açısından bu alanların üzerinde önemle durulması gerekli olduğu ileri sürülebilmektedir.Anahtar Kelimeler: Küreselleşme, Kent Yoksulluğu, Yeni Kentsel Yoksulluk Kapitalizm.

Poverty is getting to be inversed more inextricable during the first years of twenty-first century with the effect of globalization process. The alternation and transformation,which is in practice in all fields,naturally reflects itself to the problems of society. Poverty phenomenon, which can be assumed as old as human beings? existence, is gaining new dimensions day after day and receive share overly especially in globalization era of changing world. Urban poverty phenomenon is becoming more and more important along with globalization. Because a great number of world?s population live in urban and the studies show that urbanization rate is predicted to increase sharply in the future. In spite of this, besides the facilities such as accomodation, nutrition, transportation, infrastructure etc. and especially the employment opportunities that urban offers are below the basic needs and future expectations of urban population and this kind of poverty that is practiced in those areas lead to more important problems. For this reason, poverty issue which deepens day by day in global world is studied in terms of urban poverty in this study. In the era of globalization, poverty phenomenon which now has new dimensions, is studied in terms of urban poverty and the individuals who live underneath the skyscrapers,in the streets,under the bridges in carton boxes,nourished with trashes and seen as potential criminals have becme one of the realities of big cities especially in global urbans.Moving here, urban poverty problem is getting to be more and more chronic social problem both in terms of national and international aspects. Global world?s urbans are the most remarkable places where the gap between whealthy and poor can be best observed..For this reason it is stated that it is a necessity to study about especially urban areas, which have a direct effect in formation and progress of poverty.Briefly,increasing urbanization rate in the global world which leads to deepening of the poverty in those areas makes it indispensable to find urgent and permanent solutions to the problem.Key Words: Globalization, Urban Poverty, New Urban Poverty, Capitalism.
A sociological approach to phenomenon of globalization and urban poverty
Keywords: Sosyoloji